Some related fixed point theorems for multivalued mappings on two metric spaces - Ö. Biçer; M. Olgun; T. Alyildiz; I. Altun (Karpatsʹkì Matematičnì Publìkacìï, 2020)
The definition of related mappings was introduced by Fisher in 1981. He proved some theorems about the existence of fixed points of single valued mappings defined on two complete metric spaces and relations between these mappings. In this paper, we present some related fixed point results for multivalued mappings on two complete metric spaces. First we give a classical result which is an extension of the main result of Fisher to the multivalued case. Then considering the recent technique of Wardowski, we provide two related fixed point results for both compact set valued and closed bounded set valued mappings via $F$-contraction type conditions.